2006
DOI: 10.14358/pers.72.3.249
|View full text |Cite
|
Sign up to set email alerts
|

A Global Assessment of the SRTM Performance

Abstract: The NASA/NGA Shuttle Radar Topography Mission (SRTM) collected interferometric radar data which has been used by the Jet Propulsion Laboratory to generate a near-global topography data product for latitudes smaller than 60°. One of the primary goals of the mission was to produce a data set that was globally consistent and with quantified errors. To achieve this goal, an extensive global ground campaign was conducted by NGA and NASA to collect ground truth that would allow for the global validation of this uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
587
5
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 914 publications
(610 citation statements)
references
References 7 publications
6
587
5
12
Order By: Relevance
“…COMrisk Report (Kystdirektoratet, 2004) Coastal compared to previously reported estimates (Rodríguez et al, 2006) since SRTM accuracy has improved since then. An important artefact introduced by the SRTM relates to the fact that the 100 m resolution does not resolve the dune profile; therefore the coastal protection in the study area is underestimated.…”
Section: Digital Elevation Modelmentioning
confidence: 80%
“…COMrisk Report (Kystdirektoratet, 2004) Coastal compared to previously reported estimates (Rodríguez et al, 2006) since SRTM accuracy has improved since then. An important artefact introduced by the SRTM relates to the fact that the 100 m resolution does not resolve the dune profile; therefore the coastal protection in the study area is underestimated.…”
Section: Digital Elevation Modelmentioning
confidence: 80%
“…Many glacier elevation change studies have used this as a base dataset to compare to both newer and older data products (Rignot et al, 2003;Berthier et al, 2004;Larsen et al, 2007;Schiefer et al, 2007;Paul and Haeberli, 2008). Typically reported vertical uncertainties of the dataset are ≈ ±10 m which is lower than the mission standards of ±16 m (Rodriguez et al, 2006). However, vertical biases are present due to instability of the sensor and/or platform (Rabus et al, 2003), and elevation-dependent biases have also been shown due to penetration of the C-band radar waves (center frequency at 5.3 GHz) into snow and ice (Rignot et al, 2001;Berthier et al, 2006).…”
Section: Interferometric Srtm Demmentioning
confidence: 99%
“…This may be accomplished by minimizing stable terrain elevation residuals using a 2-D linear regression, e.g. iteratively shifting one DEM to the other within a ±5 pixel window (Rodriguez et al, 2006;Berthier et al, 2007;Howat et al, 2008). Other studies have corrected DEMs using single or multiple linear regression corrections between elevation and the location and terrain parameters (Gorokhovich and Voustianiouk, 2006;Bolch et al, 2008;Peduzzi et al, 2010).…”
mentioning
confidence: 99%
“…The SRTM DEM of Kerguelen Islands (downloaded from ftp:// e0srp01u.ecs.nasa.gov, SRTM3, version 2) is characterized by a small percentage of data voids ($1%). Although SRTM is a global product, previous studies reported some significant regional differences in its accuracy [Berthier et al, 2006;Rodriguez et al, 2006;Surazakov and Aizen, 2006]. Thus, SRTM errors need to be determined on stable ice-free land before any glaciological application.…”
Section: Srtm Dem and Icesat Elevation Profilesmentioning
confidence: 99%